Amine skeleton-based c-di-GMP derivatives as biofilm formation inhibitors. (15th January 2021) - Ikeda, Kentaro; Yanase, Yuta; Hayashi, Katsuhiko; Hara-Kudo, Yukiko; Tsuji, Genichiro; Demizu, Yosuke
Graphical abstract: Abstract: Bacteria can form a biofilm composed of diverse bacterial microorganism, which work as a barrier to protect from threats, such as antibiotics and host immunity system. The formation of biofilms significantly impairs the efficacy of antibiotics against pathogenic bacteria. It is also a serious problem to be solved that the emergence of multidrug-resistant bacteria (such as methicillin-resistant Staphylococcus aureus, MRSA) accelerated by the overuse of antibiotics. Therefore, the usage of biofilm inhibition agents has attracted immense interest as a novel strategy for treatment of diseases related to bacterial infection. From the difference of mode of action against bacterial cells, biofilm inhibition agents are expected to circumvent the emergence of multidrug-resistant bacteria. In this study, we have developed the derivatives of c-di-GMP, a kind of cyclic dinucleotide that is expected to have the effect of inhibiting bacterial biofilm formation. Some of the synthesized derivatives were found to inhibit biofilm formation of Gram-positive bacteria.